2010
DOI: 10.1021/jo101043m
|View full text |Cite
|
Sign up to set email alerts
|

A Solanesol-Derived Scaffold for Multimerization of Bioactive Peptides

Abstract: A flexible molecular scaffold bearing varying numbers of terminal alkyne groups was synthesized in five steps from solanesol. R(CO)-MSH(4)-NH 2 ligands, which have a relatively low affinity for binding at the human melanocortin 4 receptor (hMC4R), were prepared by solid phase synthesis and were N-terminally acylated using 6-azidohexanoic acid. Multiple copies of the azide N 3 (CH 2 ) 5 (CO)-MSH(4)-NH 2 were attached to the alkyne-bearing, solanesol-derived molecular scaffold via the copper(I)-catalyzed azide-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(44 citation statements)
references
References 52 publications
(53 reference statements)
2
42
0
Order By: Relevance
“…Volatiles were removed under vacuum and the resultant slurry subjected to flash column chromatography using a mobile phase of 10% MeOH/CHCl 3 . Product-containing fractions were combined and solvents removed in vacuo to give 11 as a white solid, mp 94–96 °C (lit 24 mp 94–96 °C). Yield 3.81 g (15.7 mmol, 75%); R f 0.38 (10% MeOH/CHCl 3 , visualization KMnO 4 ); 1 H NMR (500 MHz, methanol- d 4 ) δ 4.47 (t, J = 5.3 Hz, 1H, CH), 3.96–3.70 (m, 2H, O-CH 2 ), 3.33 (t, J = 6.9 Hz, 2H, N 3 -CH 2 ), 2.34 (t, J = 7.5 Hz, 2H, CH 2 ), 1.67 (m, 4H, overlapped CH 2 ), 1.56–1.35 (m, 2H, CH 2 ); 13 C NMR (125 MHz, methanol- d 4 ) δ 175.98 (CO), 175.09 (CO), 63.11, 56.43, 52.27, 36.62, 29.61, 27.35, 26.21.…”
Section: Methodsmentioning
confidence: 99%
“…Volatiles were removed under vacuum and the resultant slurry subjected to flash column chromatography using a mobile phase of 10% MeOH/CHCl 3 . Product-containing fractions were combined and solvents removed in vacuo to give 11 as a white solid, mp 94–96 °C (lit 24 mp 94–96 °C). Yield 3.81 g (15.7 mmol, 75%); R f 0.38 (10% MeOH/CHCl 3 , visualization KMnO 4 ); 1 H NMR (500 MHz, methanol- d 4 ) δ 4.47 (t, J = 5.3 Hz, 1H, CH), 3.96–3.70 (m, 2H, O-CH 2 ), 3.33 (t, J = 6.9 Hz, 2H, N 3 -CH 2 ), 2.34 (t, J = 7.5 Hz, 2H, CH 2 ), 1.67 (m, 4H, overlapped CH 2 ), 1.56–1.35 (m, 2H, CH 2 ); 13 C NMR (125 MHz, methanol- d 4 ) δ 175.98 (CO), 175.09 (CO), 63.11, 56.43, 52.27, 36.62, 29.61, 27.35, 26.21.…”
Section: Methodsmentioning
confidence: 99%
“…Solanesol-derived and sucrose-derived scaffolds were utilized to make both bivalent and tetravalent ligands attached to the His-DPhe-Arg-Trp tetrapeptide sequence [270, 271]. Moderate improvement in binding affinity at the hMC4R was observed, likely due to proximity effects and increasing the moles of pharmacophore present, but not indicative of cooperative or multivalent binding.…”
Section: Bivalent and Multivalent Melanocortin Ligandsmentioning
confidence: 99%
“…Moderate improvement in binding affinity at the hMC4R was observed, likely due to proximity effects and increasing the moles of pharmacophore present, but not indicative of cooperative or multivalent binding. The authors hypothesized their ligands may not possess the correct linker length or improperly presented the pharmacophores for cooperative binding [270, 271]. …”
Section: Bivalent and Multivalent Melanocortin Ligandsmentioning
confidence: 99%
“…Wang et al (2003aWang et al ( , b, 2005) synthesised a number of solanesol derivatives and found several compounds with good antitumour activities. Alleti et al (2010) synthesised a solanesol-derived scaffold bearing varying numbers of terminal alkyne groups for multimerisation of bioactive peptides. Recently, Xiao et al (2012) synthesised 12 diacid solanesyl tegafur esters by the reaction of solanesol with four acid anhydrides and N-alkoxy-tegafur; the preliminary bioassay results showed that these target compounds possess antitumour activities to some extent.…”
Section: Coenzyme Q10 and Vitamin K2mentioning
confidence: 99%